2018
DOI: 10.1037/pac0000268
|View full text |Cite
|
Sign up to set email alerts
|

Practice the change you want to see in the world: Transformative practices of social movements in Israel.

Abstract: This study explores the psychological challenges to social movements in the face of structural and cultural violence, and the cognitive and behavioral practices that help overcome these obstacles. It presents 3 case studies of social movements that brought about political and social transformation in Israel in the past 15 years: the struggles against industrial pollution in the city of Ashkelon; for the rights of the LGBT movement in Jerusalem; and of young Jews and Palestinians working against institutional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…David and Rubel-Lifschitz (2018) presented a case study that explored how groups can overcome challenges involved in social change movements involving unjust, violent social structures. The case study took place in Israel and utilized the research tradition of conflict transformation.…”
Section: Community Occurrence: a Struggle Concerning A Polluting Plant In Southern Israelmentioning
confidence: 99%
See 4 more Smart Citations
“…David and Rubel-Lifschitz (2018) presented a case study that explored how groups can overcome challenges involved in social change movements involving unjust, violent social structures. The case study took place in Israel and utilized the research tradition of conflict transformation.…”
Section: Community Occurrence: a Struggle Concerning A Polluting Plant In Southern Israelmentioning
confidence: 99%
“…The case study took place in Israel and utilized the research tradition of conflict transformation. “The conflict transformation tradition suggested that transformation from unjust unequal structures to equal just structures should occur through practices of power with others as opposed to power over others ” (David & Rubel-Lifschitz, 2018, p. 11). The ability to engage people in power with others involves identifying people with shared ideas who set “goals that use resources to promote those goals, for the sake of all members of society.…”
Section: Community Occurrence: a Struggle Concerning A Polluting Plant In Southern Israelmentioning
confidence: 99%
See 3 more Smart Citations